HIV/AIDS, TO DISCLOSE OR NOT TO DISCLOSE: THAT IS THE QUESTION - Andra le Roux-Kemp (Potchefstroom Electronic Law Journal, 2013)
The systemic consequences of the HIV/AIDS pandemic in South Africa are evident not only in demographic, economic and social trends, but also on a micro- and personal level, where they are devastating. Those infected with HIV are often the target of intense discrimination and discriminatory behaviour including rejection, isolation and violence. It is especially because of these macro- and micro effects associated with HIV/AIDS that the highest regard should be placed on the fundamental rights of infected individuals - specifically the rights to privacy and bodily and psychological integrity - when determining if the disclosure of such persons’ status is necessary and justified. The primary aim of this article is to critically consider and describe the different contexts in which the disclosure of a person’s HIV/AIDS status will be relevant. The position of various role players in the economy, in the criminal justice system and in the healthcare arena will be considered with reference to relevant legislation, case law, guidelines and ethical codes. It will be clear from the discussion that no simple or single right answer exists. A patient-oriented approach sensitive to public health goals and objectives and based on human rights principles is advocated in this article.